The Purchasing Decisions of Organic Vegetables at Outlets in Denpasar City - Ni Kadek Ririn Diana; Made Antara; Widhianthini Widhianthini (Universitas Udayana, 2020)
The agricultural is the sector with the greatest strength in Indonesia. One of the potential agricultural products in Indonesia is vegetables. In our life, vegetables play an important role, such as fulfilling our food needs and improving the nutrition. It is because they are one of the sources of minerals, vitamins, fiber, antioxidants and energy needed by our body. Organic vegetables are horticultural commodities which have advantages of being free from pesticide residues and other dangerous chemicals. Nowadays, it becomes a trend among the community as a form of a healthy lifestyle. This study is aimed at analyzing the marketing mix system and the factors that influence the purchase of organic vegetables at outlets in Denpasar City. The technique of determining the sample in this study was done by accidental sampling, and it obtained 60 respondents. SEM-PLS is used as the technique of analyzing data. The results showed that the marketing mix system at the outlets in Denpasar City had implemented 5 variables, namely product, price, place, promotion and physical evidence, significantly, those 5 variables influenced the decision in purchasing organic vegetables.